The Role of Parents in Cultivating Empathy and Social Concern in Early Childhood through the Habituation of Friday Charity (Sedekah Jum’at) - Hani Putri Nadia; Muhammad Yusuf; Yuning Eka Rahma Wati; Choirudin Choirudin (Bulletin of Early Childhood, 2025)
This study aims to examine the implementation of the Friday Charity (Sedekah Jumat) habituation program, the role of parents, and its impact on the development of empathy and social care in children aged 5–6 years at RA Bustanul „Ulum Jayasakti. This research is motivated by the presence of egocentric behavior and a lack of social concern among some early childhood students. This study employs a qualitative approach with a descriptive method. The research subjects include the principal, Group B teachers, and parents. Data were collected through observation, interviews, and documentation, while data analysis was conducted through data reduction, data display, and conclusion drawing. The results show that the Friday Charity habituation program is implemented regularly as part of character education. The role of parents is crucial, particularly through role modeling, providing understanding, and reinforcing values at home. Children who receive active parental guidance demonstrate better development of empathy, such as sharing and showing concern for others, while those who receive less support tend not to display optimal empathetic behavior. In conclusion, the Friday Charity habituation program is effective in fostering empathy and social care in early childhood when supported by active parental involvement and collaboration with the school.